Die afbuiging van Calvyn se denke in die 17e eeu - Schulze, L.F. (Koers, 1983)
The period of the Reformation was in certain aspects a lonely beacon in the cultural history of Western civilization. I his fact is illuminated by comparing the anti scolastic stand of Luther and Calvin, and especially Calvin's trinitarian view o f revelation with its ensuing knowledge, of God with the views of Perkins and Ames, in whose works tendencies towards a natural knowledge of God become discernable. Though the language of the later theologians remains “calvinistic”, yet there is a dear shift of accent in the whole theological structure o f their works and a growing emphasis on subjectivity.